Evaluation the role of Interlukin-36 in Atopic dermatitis patients (Eczema) - Jehad, Thahab Majeed; Al-Watar, Wifaq M.; Fadhel, Basman Medhat (Journal of Neonatal Surgery, 2025)
Background: Atopic dermatitis (atopic eczema) is a widespread inflammatory skin condition characterized by defects in both skin barrier structures and immune response alternations, so that the major cause for structural abnormalities in the epidermidis associated with immune dysregulation in this disease. Objective: This study aimed to compare serum IL-36α between 3 study groups and the involvement and importance of these interleukins in atopic dermatitis. Method: ELISA was used to detect the IL-36 level between groups under study. During the current study, blood samples, were collected from only 60 patients with AD in Diyala and Baghdad province, and 30 healthy persons as a control. Results: there were significant differences between patients age groups, the highest mean of infection was in the patients and under 30 age categories while the lowest infection mean in control group. the statistical analysis shows the mean of IL-36 in non-treated and treated groups increased significantly when compared with control group. In non-exposure groups IL-36 increased significantly when compared with control group. In Hands & Foot, and Back & Chest groups IL-36 increased significantly when compared with control. The statistical analysis shows the mean of IL-36 in acute, and chronic groups increased significantly when compared with control. The mean of IL-36 in generalized, and localized groups increased significantly when compared with control group. In topical steroid, and systemic groups IL-36 increased significantly when compared with control group. p-value was less than 0.05. Conclusion: The study demonstrates the role of IL-36 in the pathogenesis of atopic dermatitis and a positive correlation between severity of AD symptoms and level of serum IL-36.